Genome-wide transcriptional regulation of estrogen receptor targets in fallopian tube cells and the role of selective estrogen receptor modulators. Issue 1 (December 2016) - Moyle-Heyrman, Georgette; Schipma, Matthew; Dean, Matthew; Davis, David; Burdette, Joanna
Abstract Background The fallopian tube epithelium is one of the potential sources of high-grade serous ovarian cancer (HGSC). The use of estrogen only hormone replacement therapy increases ovarian cancer (OVCA) risk. Despite estrogen's influence in OVCA, selective estrogen receptor modulators (SERMs) typically demonstrate only a 20 % response rate. This low response could be due to a variety of factors including the loss of estrogen receptor signaling or the role of estrogen in different potential cell types of origin. The response of fallopian tube epithelium to SERMs is not known, and would be useful when determining therapeutic options for tumors arising from this cell type, such as HGSC. Results Using normal murine derived oviductal epithelial cells (mouse equivalent to the fallopian tube) estrogen receptor expression was confirmed and interaction with its ligand, estradiol, triggered mRNA and protein induction of progesterone receptor (PR). The SERMs 4-hydroxytamoxifen, raloxifene and desmethylarzoxifene, functioned as estrogen receptor antagonists in oviductal cells. Cellular proliferation and migration assays suggested that estradiol does not significantly impact cellular migration and increased proliferation. Further, using RNAseq, the oviduct specific transcriptional genes targets of ER when stimulated by estradiol and 4-hydroxytamoxifen signaling were determined and validated. The RNA-seq revealed enrichment in proliferation, anti-apoptosis, calcium signaling and steroid signaling processes. Finally, the ER and PR receptor status of a panel of HGSC cell lines was investigated including Kuramochi, OVSAHO, OVKATE, OVCAR3, and OVCAR4. OVSAHO demonstrated receptor expression and response, which highlights the need for additional models of ovarian cancer that are estrogen responsive. Conclusions Overall, the fallopian tube has specific gene targets of estrogen receptor and demonstrates a tissue specific response to SERMs consistent with antagonistic action.